A new Baurusuchidae (Notosuchia, Crocodyliformes) from the Adamantina Formation (Bauru Group, Upper Cretaceous), with a revised phylogenetic analysis of Baurusuchia - Martins, Kawan Carvalho [UNESP]; Queiroz, Marcos Vinicius Lopes [UNESP]; Ruiz, Juan Vítor [UNESP]; Langer, Max Cardoso; Montefeltro, Felipe Chinaglia [UNESP] (Elsevier, 2024)
Baurusuchidae is a group of notosuchian crocodyliforms ubiquitous to South American Upper Cretaceous deposits. They are distinguished by having dog-faced skulls, reduced tooth rows, and hypertrophied caniniforms. Here, we describe a new baurusuchid from the Adamantina Formation (Bauru Group), in Southeast Brazil. The new taxon consists of a right portion of the skull, cranial roof elements, fragments of the secondary palate and the lower jaw, as well as six isolated teeth. The specimen is assigned to the genus Aphaurosuchus due to the presence of a posterior depression on the nasal and upturned infraorbital jugal ridge. A new species, Aphaurosuchus kaiju, was erected based on characters that distinguish it from Aph. escharafacies, such as a large and deep depression occupying most of the dorsal surface of the frontal, a midline longitudinal depression on the anteriormost portion of the frontal, a well-developed crest concealed in the frontal depression, and a smooth parietal near the supratemporal fenestrae. We investigated the affinities of Aphaurosuchus kaiju and recently described/revised putative baurusuchians by performing an updated phylogenetic analysis that combined information from the three most up to date datasets available. We recovered the two main lineages of Baurusuchidae, Pissarrachampsinae and Baurusuchinae, with its traditional subset of taxa, but also recovered Ogresuchus furatus (Maastrichtian of Europe) and Razanandrongobe sakalavae (Batesian of Madagascar) as non-baurusuchid baurusuchians. In the light of our results, the inclusion of these two taxa in an otherwise well stablished Baurusuchia suggests that this clade had much broader spatial and temporal distributions than initially thought.
Keywords: Adamantina Formation; Aphaurosuchus; Bauru Basin; Baurusuchia; Baurusuchidae